The Dynamic Approach of Education: Focus on Educational Actions and Subsequent Evaluations - Anca Simion; Cristian Stan (Babes-Bolyai University, 2023)
This paper explores the multifaceted nature of the educational process, focusing on the complex connections between educational actions, the dynamic nature of education, and subsequent evaluations. With a primary focus on primary school settings, the current paper tries to acknowledge the pivotal role of teachers' approaches to education in shaping students' learning experiences. It recognizes the significant influence of teacher discourse and the classroom dynamic on students' academic progress. Through this review of the existing literature, we examine ongoing discussions surrounding how pupils are influenced by various teaching interactions. We tried to highlight the importance of understanding the complexity of the educational journey, recognizing that in a rapidly evolving world, the student remains at the heart of education and evaluation approaches. The paper emphasizes the need to consider the holistic educational experience, encompassing teaching techniques, classroom dynamics, and students' receptiveness to instruction. The paper presents an understanding of how teachers' instructional approaches and classroom dynamics shape students' learning outcomes and performance assessments. By recognizing the central role of the pupil in the educational journey, this study contributes to the ongoing discourse on effective teaching practices and student-centered evaluation approaches.